2008
DOI: 10.1093/bioinformatics/btn574
|View full text |Cite
|
Sign up to set email alerts
|

Shortest path analysis using partial correlations for classifying gene functions from gene expression data

Abstract: Motivation: Gaussian graphical models (GGMs) are a popular tool for representing gene association structures. We propose using estimated partial correlations from these models to attach lengths to the edges of the GGM, where the length of an edge is inversely related to the partial correlation between the gene pair. Graphical lasso is used to fit the GGMs and obtain partial correlations. The shortest paths between pairs of genes are found. Where terminal genes have the same biological function intermediate gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The most highly connected nodes were FEV1 and Gas Trapping (see Figure 1), with Gas Trapping significantly connected with all of the analyzed phenotypes. In addition, the 16 pairs that were not directly connected (p-values >0.001) were connected through only one transitive node based on shortest path analysis [18]. The majority of shortest paths connected through gas trapping (9 out of 16), suggesting that gas trapping is a “hub” in the phenotypic network.…”
Section: Resultsmentioning
confidence: 99%
“…The most highly connected nodes were FEV1 and Gas Trapping (see Figure 1), with Gas Trapping significantly connected with all of the analyzed phenotypes. In addition, the 16 pairs that were not directly connected (p-values >0.001) were connected through only one transitive node based on shortest path analysis [18]. The majority of shortest paths connected through gas trapping (9 out of 16), suggesting that gas trapping is a “hub” in the phenotypic network.…”
Section: Resultsmentioning
confidence: 99%
“…The problem of finding the shortest distance between two vertices of a graph and finding a path that causes it are classic problems in graph algorithms. It appears in countless practical applications and is an important concept in transportation (and communication) engineering, computer science, network routing, network analysis [63], image processing [37,61], operation research [19, pages 657], VLSI design [66], DNA analysis [70], bio-informatics [39], chemical compounds [6,31], computational geometry and robotics [33], to mention few central areas of interest. Because of its rich in applications, the work on such problems are deep and vast (in all kinds of classic graphs, directed or undirected, weighted or unweighted), in both the scientific community and engineering community.…”
Section: Motivationmentioning
confidence: 99%
“…It has been shown that genes or proteins with high network proximity tend to have similar biological functions [52] and several methods have been developed to predict gene function exploiting the colocalization of functionally annotated genes with genes of unknown function [53][54][55][56]. Network proximity can also be used as a predictor for genes implicated in disease processes [57,58].…”
Section: Using Network To Understand Diseasesmentioning
confidence: 99%